Efficient CRISPR/Cas9-mediated genome editing of phytoene desaturase in Musa-AAA: a critical step for genetic improvement of east African highland bananas - Kalungi, Frank; Mulindwa, Julius; Muiruri, Samwel Kariuki; Ntui, Valentine Otang; Mustafa, Abubakar Sadik; Namanya, Priver Bwesigye; Kubiriba, Jerome; Tripathi, Leena; Barekye, Alex; Tindamanyire, Jimmy Moses (Frontiers in Plant Science, 2025)
East African highland bananas (EAHBs), locally referred to as “matooke”, are an important staple crop in Uganda. The EAHBs have a triploid genome (AAA) with a large phenotypic diversity in the Great Lakes region of Africa and are challenged by both abiotic and biotic factors. The EAHBs have been improved through conventional breeding and genetic engineering though facing challenges such as genetic drag of unfavorable traits and complex regulatory processes, respectively. Therefore, a more precise approach for crop improvement such as genome editing is highly recommended. In the current study, we assessed the feasibility and applicability of the CRISPR/Cas9 mediated-genome editing in EAHBs. Two sgRNAs were designed from the Nakitembe phytoene desaturase (PDS) gene and used to edit the PDS gene in Nakitembe (NKT) and NAROBan5 (M30) cultivars. A total of 47 NKT and 130 M30 events were regenerated via agrobacterium-mediated transformation of banana embryogenic cell suspensions. Up to 100% and 94.6% albinism rates were observed in Nakitembe and M30 cultivars respectively with additional albino-variegated and variegated phenotypes observed in M30 only. Carotenoid analysis revealed a significant reduction of total carotenoid content in edited events with all complete albinos showing no detectable carotenoids implying that the carotenoid biosynthetic pathway was effectively disrupted. Sequence analysis revealed that all of the edited events had frameshift mutations leading to PDS disruption. Overall, this study presents the first report of CRISPR/Cas9 genome editing in EAHBs and more interestingly on a hybrid, M30 showing high precision and efficiency. This validated genome editing system provides a robust platform for targeted EAHB improvement.